2011
DOI: 10.1007/s11325-011-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between high-sensitivity C-reactive protein levels and the severity of obstructive sleep apnea

Abstract: Patients with OSA have elevated serum levels of hs-CRP, a marker for inflammation and an independent risk predictor for cardiovascular morbidity. The severity of OSA is responsible for the elevation of hs-CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 32 publications
0
37
1
Order By: Relevance
“…[424344] However, other authors concluded that CRP, TNF-α, and IL6 levels in patients with OSAHS are elevated, independently of obesity, and are related to increased metabolic and cardiovascular diseases, sleepiness, and fatigue. [45464748] In our study, there is no association between IL-17, VD, and BMI. Hence, it can be hypothesized that OSAHS is associated with VD deficiency and serum levels of IL-17 increase independently of obesity.…”
Section: Discussioncontrasting
confidence: 62%
“…[424344] However, other authors concluded that CRP, TNF-α, and IL6 levels in patients with OSAHS are elevated, independently of obesity, and are related to increased metabolic and cardiovascular diseases, sleepiness, and fatigue. [45464748] In our study, there is no association between IL-17, VD, and BMI. Hence, it can be hypothesized that OSAHS is associated with VD deficiency and serum levels of IL-17 increase independently of obesity.…”
Section: Discussioncontrasting
confidence: 62%
“…In OSAS patients, several inflammatory factors can be found in high concentrations, which can be used as biological markers [32], such as interleukin-6 (IL-6) [33], interleukin-8 (IL-8) [34,35], tumor necrosis factor-α (TNF-α) [35], vascular endothelial growth factor (VEGF) [36], leptine [37,38], and C-reactive protein (CRP) [39,40].…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Some studies have identified an independent association between sleep characteristics (namely, disordered breathing, duration, and quality ratings) and inflammation (22-33). Other studies have reported that associations between these sleep characteristics and inflammation are accounted for by confounders like disease and adiposity (34-39)).…”
mentioning
confidence: 99%